Long (MIS 5e – 3) environmental history of a paleolake in central Poland recorded in the succession from Kubłowo. (20th February 2018) - Mirosław-Grabowska, Joanna; Niska, Monika; Roman, Małgorzata
Abstract: One of the longest (above 7 m thick) uninterrupted Eemian-Vistulian (Weichselian) pollen successions in Poland is known from Kubłowo (central Poland). The huge importance of this succession is manifested in the possibility of study the evolution of the lake environment under the influence of changing, from interglacial to glacial climatic conditions. The reconstruction of the environmental changes at Kubłowo and its surroundings show the short climate fluctuations and a detailed picture of the natural conditions prevailing in central Poland (central Europe) during the period from approximately 126, 000 to 55, 000 years BP. Based on the results of multi-proxy analysis, four lacustrine stages linked with a higher water level and three boggy stages (low water level) of evolution of the Kubłowo paleolake were observed. The pollen diagram from Kubłowo reveals a succession of eighteen local pollen assemblage zones (K1-K18 L PAZ). The K1 to K7 LPAZ zones record the interglacial succession correlated with the Eemian. The next pollen zones, K8 to K18, are linked with the Vistulian. The pollen sequence shows, between the Eemian Interglacial (MIS 5e) and the last glaciation (second stadial of the Plenivistulian (MIS 4-3), four cold intervals that are interpreted as stadial phases: Herning, Rederstall, Schalkholtz and Ebersdorf separated by three temperate intervals (interstadials): Brörup, Odderade and Oerel. In the studied sediments, 25 species of subfossil Cladocera were identified, and ten zones of fauna development were distinguished. The unique feature of this profile is the good preservation of above 100, 000-year-old Cladocera remains and a high diversity of species, which are primarily littoral. The Middle and Late Eemian were periods convenient to Cladocera development due to high temperatures, high water levels, high trophy and occurrence macrophytes. A deterioration of fauna living conditions started in the Late Eemian and next took place in the Vistulian cold events. The results of isotopic and geochemical analyses of organic matter from Kubłowo have enabled the reconstruction of varying environmental conditions and the origin of organic matter. The organic carbon content (TOC) changes from 1% to 40% and is closely related to climatic conditions. During the Eemian, the amount of TOC systematically increased. The lowest values are recorded in the coldest periods during the Herning, Rederstall and Schalkholz Stadials. The C/N atomic ratio fluctuates from 13 to 34 and the highest values occur in the Brörup Interstadial. The values of δ 13 C change from −27.9 to −12.9‰, and δ 15 N values oscillate between −1.6 and +5.3‰.